Water-assisted flash sintering: Flashing ZnO at room temperature to achieve ~ 98% density in seconds. (1st January 2018) - Nie, Jiuyuan; Zhang, Yuanyao; Chan, Jonathan M.; Huang, Rongxia; Luo, Jian
Abstract: Water can trigger flash sintering of ZnO powder pellets at room temperature to achieve ~ 98% of the theoretical density in 30 s without any external furnace heating. The specimen conductivity can be increased by > 10, 000 times via absorbing water vapor to enable the room-temperature flash. The initial electric field must be higher than a critical threshold to lead to densification, suggesting bifurcation in kinetic pathways. This new cost and energy saving water-assisted flash sintering (WAFS) technology can potentially be applied to consolidate other ceramic materials. Graphical abstract: